THE EFFECT OF JOB SATISFACTION, ORGANIZATIONAL COMMITMENT AND WORK MOTIVATION TO ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TEACHERS IN SMAN 9 TANGERANG - Maswanih Wanih; Muhammad Iqbal (Dinasti International Journal of Education Management And Social Science, 2020)
This research aims to examine and analyze the effect of job satisfaction, organizational commitment and work motivation on the organizational citizenship behavior of teachers in SMA Negeri 9 Tangerang. The study approach is a quantitative approach through data collection method using a questionnaire with a sample of 56 respondents with the sampling technique used is census. The method of analysis used is multiple linear regression conducted through SPSS software version 25. The results show that the variables of job satisfaction, organizational commitment and work motivation partly have a positive and significant effect on organizational citizenship behavior. At the same time, all three variables independent of job satisfaction, organizational commitment and job motivation have a positive and significant impact on organizational citizenship behavior teacher at SMA Negeri 9 Tangerang